Exploring English Communication Needs in A Tourism Village: What Do the Local Communities Say? - Suprina, Rina; Rahayu, Nurti; Sembiring, Vienna Artina (Institut Pariwisata dan Bisnis Internasional, 2023)
Local community empowerment in tourism villages is required to enhance community participation in community-based tourism (CBT). English learning programs in tourist villages are generally carried out as incidental community service programs. Because of time constraints and insufficient methods, the results are subpar. Therefore, an effective and efficient English learning model designed specifically to improve the communicative competence of the community managing tourist villages is required. This study aims to bridge government programs to improve tourism human resources, particularly in the community of Cibuntu, a tourist village in Kuningan Regency. The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) is used as a reference and conceptual framework in this study. This study intends to carry out the first stage of the ADDIE model, namely the Analysis stage, to identify the English needs of the Cibuntu community. To this end, a descriptive qualitative research method was employed. The information was harnessed by observing and interviewing members of local communities who involved in tourism activities. In addition, interviews with the local tourism office were conducted to determine the profile of foreign tourists. The results demonstrated the community's need for English competence, their current English skill, and the English skills they wish to achieve. Based on the results of the needs analysis stage, the next stage of ADDIE should be carried out in the future research.